Partnering with the CIO : the future of IT sales seen through the eyes of key decision makers - Minelli, Michael, 1974-; Barlow, Mike (John Wiley & Sons, 2007)
CIOs spend more than $1.2 trillion on software and hardware each year. Partnering with the CIO looks at IT sales from the CIOs perspective, revealing what needs to be changed and expressing their fears, concerns, warnings, and advice.